Research of characteristics of spatial and temporal variations of CH4 emission at the water-gas interface of the Inner Mongolia section of the Yellow River and its influencing factors - Hongxia Bao; Yue Lang; Narentuya; Fang Liu; Liming Qi; Xiaoli Wang (Journal of Freshwater Ecology)
It is widely recognized that rivers serve as significant sources of greenhouse gas emissions. However, the monitoring and analysis of factors influencing methane (CH4) emissions from the Yellow River remain inadequate, particularly regarding high-frequency and detailed temporal differentiation studies. This study selected six sampling points in the Inner Mongolia section of the Yellow River (IMYR) to investigate the spatio-temporal variations in CH4 flux (FCH4) and CH4 concentration (CCH4) at the water-gas interface, along with their influencing factors. The results indicate that the range of FCH4 at the gas-water interface in IMYR is −30.41 to 84.75 mg·m−2·d−1. The CCH4 in water varies from 0.07 to 0.22 μmol·L−1, indicating an overall ‘source’ effect on atmospheric CH4. Both FCH4 and CCH4 exhibit higher values in summer and lower in spring, primarily driven by temperature fluctuations. Significant spatial differentiation of FCH4 and CCH4 is observed in the Inner Mongolia section of the Yellow River, with the highest CCH4 and FCH4 values recorded in Baotou (BT) and Wuhai (WH), respectively. On a seasonal scale, dissolved oxygen (DO) and water temperature (Tw) are the primary determinants affecting CH4 emissions. Given its importance within freshwater ecosystems, greater attention should be paid to CH4 emissions from river ecosystems.